Multiple linear modelling in revealing the relationship between learning styles and mathematics performance - Nurcahya Binti Abdul Rashid; Siti Rahayu Binti Mohd Hashim; Mohd Khairuddin Abdullah@Jerry (Human Resource Management Academic Research Society, 2025)
Learning style refers to individuals concentrating on processing, internalizing, and retaining new and challenging academic information. Mathematics achievement is a level or nature of proven learning in a specific mathematical topic. It is a construct that shows how well someone has mastered mathematical ideas and abilities. This study intends to determine significant factors that contribute to mathematics achievement and learning styles in mathematics. The factors included were parental education and household income. The secondary objective of the research is to determine the relationship between learning style and mathematics achievement. Student’s mathematics achievement was measured using their final academic session examination results. This study involved 246 form four students from Kinabatangan secondary school and was stratified into three levels of mathematics achievement: good, moderate and poor. Pearson Chi-square analysis confirmed a significant association between learning styles and mathematics achievement, showing that reflector learners tend to perform better in mathematics. In contrast, activist learners tend to perform lower in mathematics. Multiple regression analysis indicated that the reflector learning style and parents' educational background significantly contribute to mathematics achievement. These findings provide valuable insights for educators and curriculum designers, highlighting the importance of customized instructional strategies to improve student learning outcomes in mathematics.